A novel poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)-PEG-melatonin composite scaffold enhances for inhibiting bone tumor recurrence and enhancing bone regeneration - Zhang, Wei-Lin; Dai, Zhi-Wen; Chen, Si-Yuan; Guo, Wei-Xiong; Wang, Zhong-Wei; Wei, Jin-Song (Frontiers in Pharmacology, 2023)
Postoperative comprehensive treatment has become increasingly important in recent years. This study was to repair tissue defects resulting from the removal of diseased tissue and to eliminate or inhibit the recurrence and metastasis of residual tumors under the condition of reducing the systemic side effects of chemotherapeutic drugs.To address these challenges, multifunctional scaffolds based local drug delivery systems will be a promising solution.We designed an optimal drug-loaded scaffold material PHBV-mPEG5k (PP5), which is biocompatible, hydrophilic and biodegradable.Furthermore, this material showed to promote bone healing, and could be conveniently prepared into porous scaffold by freeze-drying the solution. By means of introducing melatonin (MT) into the porous surfaces, the MT loaded PP5 scaffold with desirable sustained release ability was successfully prepared.The effectiveness of the MT loaded PP5 scaffold in promoting bone repair and anti-tumor properties was evaluated through both in vivo and in vitro experiments. The results suggest that this MT loaded PP5 scaffold is able to achieve the desired outcome of bone tissue repair and anti-bone tumor properties. Furthermore, our study demonstrate that the PP5 scaffold was able to enhance the anti-tumor effect of melatonin by improving cellular autophagy, which provided a therapeutic strategy for the comprehensive postoperative treatment of osteosarcoma.